2017
DOI: 10.5005/jp-journals-10005-1458
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Syringe: A Gimmick in Pediatric Dentistry

Abstract: Aim:The management of pain and anxiety in dentistry encompasses a number of procedural issues, including the delivery of anesthetic solution. One of the most important ways to manage the behavior of children is pain control. Trypanophobia is very common among dental patients and the most important goal of guidelines on behavior guidance for pediatric dental patient is to ease fear and anxiety in dental procedures in children. For the stated reasons, the purpose of the present study was to record child's pain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…In the current study there was no significant difference in pain perceived by male and female patients. This was the same in the study by Kaur et al 7 and Janani and Kumar 15 where no significant differences were found between pain scores for men and women receiving dental anesthesia. However another study shows that gender has an important role to play in pain perception with women more likely to experience more pain with the same stimulus than men 16 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the current study there was no significant difference in pain perceived by male and female patients. This was the same in the study by Kaur et al 7 and Janani and Kumar 15 where no significant differences were found between pain scores for men and women receiving dental anesthesia. However another study shows that gender has an important role to play in pain perception with women more likely to experience more pain with the same stimulus than men 16 .…”
Section: Discussionsupporting
confidence: 83%
“…Recent literature shows a comparison of 30 gauge needles (ultrashort disposable insulin syringes) with conventional needles (27 G, 26 G) in pediatric patients. In 2017 Kaur et al 7 reported a significantly lower pain score with use of a 30 G disposable syringe. Same was observed by Alexander et al 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wand ve geleneksel enjeksiyon tekniklerinin karşılaştırıldığı bir başka çalışmada ise 21 , yaş ortalaması 14,8 (12,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)8) olan 17'si kız (%61) 28 hastanın ağrı değerlendirilmesinde görsel analog skalası kullanılarak, Wand'ın daha az kaygıya neden olduğu belirlenmiştir. 2018 yılında Libonati ve ark.…”
Section: ) Comfort Control Syringe Anesteziunclassified